Investigating the efficacy of osimertinib and crizotinib in phase 3 clinical trials on anti-cancer treatment-induced cardiotoxicity: are real-world studies the way forward?. (April 2023) - Kobat, Hasan; Elkonaissi, Islam; Foreman, Emma; O'Brien, Mary; Dorak, Mehmet Tevfik; Nabhani-Gebara, Shereen
Background: Oncology clinical trials demonstrate the risk of cardiotoxicity but are not sufficient to reveal the true risk. In this article, we compared the incidence of cardiotoxicity of crizotinib and osimertinib from a real-world study to data reported by phase 3 clinical trials. Methods: Data from an ongoing real-world lung cancer study was used as a comparator. Patients were recruited retrospectively with the criteria of being diagnosed with non-small cell lung cancer and having received at least a course of treatment of tyrosine-kinase inhibitor and/or immune check-point inhibitor. Characteristics of the patients who developed cardiotoxicity associated with osimertinib and crizotinib in the real-world lung cancer study were analysed against the inclusion criteria of the corresponding phase 3 clinical trials. Variations of cardiotoxicity incidence among the real-world lung cancer study and clinical trials were investigated. Results: 18%, n = 37/206, of the patients developed cardiotoxicity. QTc prolongation was the most frequently observed cardiotoxicity (n = 12/37). Osimertinib and crizotinib were the most cardiotoxic agents, each responsible for seven cases of cardiotoxicity. FLAURA, AURA3, PROFILE 1007 and PROFILE 1014 were the included clinical trials for analysis. None of the patients who developed cardiotoxicity in the real-world study would have been eligible to participate in FLAURA and PROFILE 1014 study whereas n = 4/7 and n = 5/7 patients were eligible to participate in AURA3 and PROFILE 1007 trials, respectively. Conclusion: Although phase 3 clinical trials play an important role in understanding the effectiveness and give insights on side-effect profiles, real-world studies can show the real risk of cardiotoxicity more accurately and realistically.